PENGARUH KUALITAS PRODUK, PROMOSI DAN BRAND IMAGE UNTUK MENINGKATKAN VOLUME PENJUALAN MOBIL MEREK SUZUKI ERTIGA DI SHOWROOM JAGORAWI MOTOR DI PANGKALPINANG - Aprilia Nurwanty; Juhari Juhari; Rita Deseria (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to determine the effect of product quality, promotion, and brand image on increasing sales. The population in this study were visitors who came to the Jagorawi Motor Showroom, while the number of samples in this study was 100 consumers of the Jagorawi Motor Showroom in Pangkalpinang. Testing in this study uses multiple linear regression analysis, analysis of the coefficient on determination, and hypothesis testing. T-test results of product quality, promotion, and brand image are obtained sig <0.05 where partially the independent variables have a positive effect on the dependent variable. F test results indicate that the independent variables jointly have a positive effect on the dependent variable accepted. The coefficient of determination (R Square) shows that product quality, promotion, and brand image can influence sales increase by 50.4%, while the remaining 49.6% is explained by other variables outside the research model.